Architecture summer schools that support community engagement - Górka Anna; Kurkowska Agnieszka (Miscellanea Geographica: Regional Studies on Development, 2025)
In this study, we focused on university-based architecture summer schools, a key component of an educational strategy for developing social cooperation to tackle climate change. During these voluntary school courses, students solve spatial problems through community collaboration. We based this study on the experiences of the Faculty of Architecture of the Gdańsk University of Technology and the European Universities of Technology Alliance (ENHANCE). It aimed to assess the performance of the summer schools and to formulate recommendations. Three surveys were conducted in which a group of 198 respondents was questioned, including students, course participants and village residents. Although respondents appreciated this educational environment, recognition and financing proved problematic. Therefore, the flow of information should be improved, and the institutional network supporting the architecture summer schools should be expanded.